The income tax nature of derivatives hedges: A critical analysis of the classification of gains made hedging a capital share investment with a single stock futures contract - Maule, James Alexander Carteret (Department of Finance and Tax, 2019)
In 1992 the Taxation Sub-Committee of the South African Institute of Chartered Accountants noted that one of the primary problems facing the taxation of derivatives used as hedges was the capital/revenue distinction, due to the fact that the application of wellestablished legal principles to these new derivative instruments and investment strategies could lead to inequitable results. Notwithstanding recommendations that special rules be developed to govern the taxation of derivatives used as hedges, little has changed. The South African Revenue Service have stated in their 2014 'Tax Guide for Share Owners’ that the sale of futures contracts is likely to be on revenue account, even if used as a hedge against losses on underlying shares held as capital assets, ostensibly on the basis that such assets derive no return for the holder and are therefore only held to be realised at a profit. This study seeks to investigate whether or not the sale of a futures contract used as a hedge against losses on an underlying share investment, held as a capital asset, should be taxed on revenue account or if in fact an argument can be made for the gain realised on the derivative to be treated as capital in nature. Against a background on the mechanics of traded futures contracts and the adopting of a 'short position’, consideration will first be given to existing South African precedent and the authority cited by SARS in support of the expressed revenue treatment. Alternative arguments proposed by writers, based on the analogous treatment of insurance proceeds or the practice of 'following the underlying asset’, will be considered against both South African and international support. This study will then consider the application of common law principles of the capital/revenue determination to identify arguments applicable to futures hedging. It is submitted that some of these common law principles identified, in particular those relating to a taxpayer’s purpose, as compared with his or her intention, would provide a cogent argument in this regard. The above findings will then be critically evaluated to determine what, on balance, the correct tax treatment in the circumstances should be bearing in mind the words of Friedman J in ITC 1450 (1988) 51 SATC 70 at 76, and Smalberger JA in CIR v Pick n Pay Employee Share Purchase Trust (1992) 54 SATC 271 at 279: 'when all is said and done, whatever guidelines one chooses to follow, one should not be led to a result in one’s classification of a receipt as income or capital which is … contrary to sound commercial and good sense.’